Patient-centred outcomes in lateral elbow tendinopathy: A systematic review of available evidence in UK populations. (December 2019) - Evans, Jonathan P; Smith, Chris; Porter, Ian; Gangannagaripalli, Jaheeda; Goodwin, Vicki; Valderas, Jose
Background: For Patient-Reported Outcome Measures to be useful, they must have evidenced reliability, validity and responsiveness in both the condition and population of interest. The aim of this study is to systematically review the evidence for Patient-Reported Outcome Measures in UK patients with lateral elbow tendinopathy. Methods: A systematic search was performed in Ovid MEDLINE, Embase and CINAHL. Studies were included if reporting administration of Patient-Reported Outcome Measures in UK populations with lateral elbow tendinopathy. Patient-Reported Outcome Measures characteristics and target populations were assessed using a structured classification system. Patient-Reported Outcome Measures reporting in randomised controlled trials was assessed against Consolidated Standards of Reporting Trials (CONSORT) standards (Patient-Reported Outcome extension). Results: A total of 16 articles were included. Out of seven different Patient-Reported Outcome Measures, there was evidence of partial validation for five. The assessment of validity, reliability and responsiveness of all Patient-Reported Outcome Measures in lateral elbow tendinopathy UK populations extended to just 20 individual patients. No articles conformed to the CONSORT Patient-Reported Outcome extension standards. Conclusion: There exists a paucity of data on the psychometrics of Patient-Reported Outcome Measures in UK lateral elbow tendinopathy populations. Without these data, trial design and interpretation are significantly hindered. The high prevalence of this condition and significant volume of studies being conducted into novel treatments highlight the need for this knowledge gap to be resolved.